2013
DOI: 10.1021/es403175d
|View full text |Cite
|
Sign up to set email alerts
|

Pacific Ciguatoxins in Food Web Components of Coral Reef Systems in the Republic of Kiribati

Abstract: Ciguatera fish poisoning (CFP) is a foodborne illness caused by consumption of coral reef fishes contaminated by ciguatoxins (CTXs); of the known CTX congeners, the Pacific ciguatoxins (P-CTXs) are the most toxic. Little is known about the trophodynamics of P-CTXs in coral reef systems. The present study explores the distribution, transfer, and trophic magnification of P-CTX-1, -2, and -3 in coral reef systems with high (ciguatoxic) and low (reference) ciguatoxicity in a CFP-endemic nation by use of liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(137 citation statements)
references
References 32 publications
(75 reference statements)
7
120
3
Order By: Relevance
“…These results are in agreement with the common knowledge of ciguatera in the region. They also corroborate a study in the Pacific that found a positive correlation between CTX1B levels and δ 15 N, suggesting biomagnification may be occurring due to biotransformation of P-CTX2 and P-CTX3 precursors (aka 52-epi-54-deoxyCTX1B and 54-deoxyCTX1B, respectively) [45]. In the Pacific, P-CTXs are known to become more potent with metabolization and oxidation as they move up the fish food chain, resulting in a greater risk of ciguatera with large predator fish [37].…”
Section: Discussionsupporting
confidence: 88%
“…These results are in agreement with the common knowledge of ciguatera in the region. They also corroborate a study in the Pacific that found a positive correlation between CTX1B levels and δ 15 N, suggesting biomagnification may be occurring due to biotransformation of P-CTX2 and P-CTX3 precursors (aka 52-epi-54-deoxyCTX1B and 54-deoxyCTX1B, respectively) [45]. In the Pacific, P-CTXs are known to become more potent with metabolization and oxidation as they move up the fish food chain, resulting in a greater risk of ciguatera with large predator fish [37].…”
Section: Discussionsupporting
confidence: 88%
“…Most of the items examining this theme were reports that stressed the inherent vulnerability of Kiribati on account of its geography, its population pressures and its problems in terms of environment, economics and isolation. Peer reviewed articles focused on the health impacts of climate change [16,23], and on food security and risks posed by climate change [24][25][26][27][28][29][30]. Migration and sociocultural issues impacted by climate change in Kiribati were also explored, further showcasing the complexity of the subject [31,32].…”
Section: Vulnerability Of Kiribati: Urbanisation Environment and Foomentioning
confidence: 99%
“…The toxins are not removed on cooking. Ciguatera seems to be of increasing concern in Kiribati, with three peer-reviewed articles exclusively focusing on the problem [27,28,30].…”
Section: Vulnerability Of Kiribati: Urbanisation Environment and Foomentioning
confidence: 99%
“…Progress has been slow for CTX (e.g., Mak et al, 2013) and PLTXlike compounds (Brissard et al, 2014;Biré et al, 2015). Ecotoxicology tests are revealing a distinctive sensitivity of model organisms to these toxins (e.g., Giussani et al, 2015).…”
Section: Improved and Reliable Detection Of Toxins In Ostreopsis And mentioning
confidence: 99%